Investigating the influence of low-level outlet shape on the scour cone formed during pressure flushing of sediments in hydropower plant reservoirs - Dreyer, Jacob Stephanus (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.